Effect of Robot-Assisted Neuroendoscopic Hematoma Evacuation Combined Intracranial Pressure Monitoring for the Treatment of Hypertensive Intracerebral Hemorrhage - Wu, Shiqiang; Wang, Heping; Wang, Junwen; Hu, Feng; Jiang, Wei; Lei, Ting; Shu, Kai (Frontiers in Neurology, 2021)
Objective: This study aimed to investigate the clinical efficacy of robot-assisted neuroendoscopic hematoma evacuation combined intracranial pressure (ICP) monitoring for the treatment of hypertensive intracerebral hemorrhage (HICH). Patients and Methods: A retrospective analysis of 53 patients with HICH undergoing neuroendoscopic hematoma evacuation in our department from January 2016 to December 2020 was performed. We divided the patients into two groups: the neuroendoscopic group (n = 32) and the robot-assisted neuroendoscopic combined ICP monitoring group (n = 21). Data on clinical characteristics, treatment effects, and outcomes were retrospectively reviewed and analyzed between these two groups. Results: The operation time of the procedure of the neuroendoscopic group was significantly longer than that of the robot-assisted neuroendoscopic combined ICP-monitoring group (mean time 153.8 ± 16.8 vs. 132.8 ± 15.7 min, P < 0.001). The intraoperative blood loss was significantly less in the robot-assisted neuroendoscopic combined ICP-monitoring group than in the neuroendoscopic group (215.4 ± 28.3 vs. 190.1 ± 25.6 ml, P = 0.001). However, the patients undergoing neuroendoscopic had a comparable hematoma clearance rate with those undergoing robot-assisted neuroendoscopic combined ICP monitoring (85.2 ± 4.8 vs. 89.2 ± 5.4%, P = 0.997). The complications rate was greater in the endoscopic group (25%) than in the robot-assisted neuroendoscopic combined ICP-monitoring group (9.5%) but without significant difference (P = 0.159). We also found that the dose of used mannitol was significantly less in the ICP monitoring group (615.2 ± 63.8 vs. 547.8 ± 65.3 ml, P < 0.001) and there was a significant difference in modified Rankin scale (mRS) score at discharge, patients with less mRS score in the robot-assisted neuroendoscopic combined ICP monitoring group than in the neuroendoscopic group (3.0 ± 1.0 vs. 3.8 ± 0.8, p = 0.011). Patients undergoing robot-assisted neuroendoscopic combined ICP monitoring had better 6-month functional outcomes, and there was a significant difference between the two groups (p = 0.004). Besides, multivariable analysis shows younger age, no complication, and robot-assisted neuroendoscopic combined ICP monitoring were predictors of 6-month favorable outcomes for the patients with HICH. Conclusion: Robot-assisted neuroendoscopic hematoma evacuation combined with ICP monitoring appears to be safer and more effective as compared to the neuroendoscopic hematoma evacuation in the treatment of HICH. Robot-assisted neuroendoscopic hematoma evacuation combined with ICP monitoring might improve the clinical effect and treatment outcomes of the patients with HICH.